Acute high-intensity aerobic exercise affects brain-derived neurotrophic factor in mild cognitive impairment: a randomised controlled study - Emer M Guinan; Kate E Devenney; Áine M Kelly; Bibiana C Mota; Cathal Walsh; Marcel Olde Rikkert; Stefan Schneider; Brian Lawlor (BMJ Open Sport & Exercise Medicine)
Objective To investigate the brain-derived neurotrophic factor (BDNF) and cognitive response to a short bout of high-intensity aerobic exercise in older adults with mild cognitive impairment (MCI).Methods Participants were randomised to one of two testing schedules, completing either a standardised exercise test (group A) or a resting control condition (group B). Blood sampling and cognitive measures (visuospatial learning and memory, sustained attention and executive function) were collected at baseline (T1) and postintervention (T2). An additional measurement of study outcomes was collected after exercise (T3) in group B only.Results 64 participants (female 53.2%, mean age 70.5±6.3 years) with MCI were recruited. From T1 to T2, serum BDNF (sBDNF) concentration increased in group A (n=35) (median (Md) 4564.61±IQR 5737.23 pg/mL to Md 5173.27±5997.54 pg/mL) and decreased in group B (Md 4593.74±9558.29 pg/mL to Md 3974.66±3668.22 pg/mL) (between-group difference p=0.024, effect size r=0.3). The control group made fewer errors on the sustained attention task compared with the exercise group (p=0.025). Measures of visuospatial learning and memory or executive function did not change significantly between groups.Conclusion This study is the first to show that a short bout of high-intensity aerobic exercise increases peripheral sBDNF in a population with MCI. However, acute exercise did not improve cognitive performance.